2010
DOI: 10.1136/bcr.02.2010.2763
|View full text |Cite
|
Sign up to set email alerts
|

Successful management of fulminant influenza A subtype H1N1 myocarditis

Abstract: SummaryThe outbreak and spread of the new influenza A subtype H1N1 reached pandemic levels during 2009, with greater numbers of cases reported daily and numerous complications described. The present report concerns an atypical manifestation of the disease in a previously healthy middleaged patient who presented with severe, refractory cardiogenic shock 4 days after being diagnosed as having influenza A. The patient was considered for emergency heart transplant. Successful treatment involved the use of a left v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 19 publications
(11 reference statements)
0
9
0
Order By: Relevance
“…There have been approximately 44 cases of influenza‐associated myocarditis in adult patients described in case reports and case series (Table ) . Among those reported, 52% (23/44) occurred in men and 68% (30/44) occurred in patients under 40 years of age.…”
Section: Resultsmentioning
confidence: 99%
“…There have been approximately 44 cases of influenza‐associated myocarditis in adult patients described in case reports and case series (Table ) . Among those reported, 52% (23/44) occurred in men and 68% (30/44) occurred in patients under 40 years of age.…”
Section: Resultsmentioning
confidence: 99%
“…Our literature review identified 75 unique cases (55 adult and 20 pediatric patients) from 56 case reports, and 5 case series describing 2 to 8 patients each, published from 1959 through 2021 [ 2 , 12 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 ,…”
Section: Resultsmentioning
confidence: 99%
“…Circulatory support consisted of inotropes/vasopressors (used in 58.7% of the cases) and MCS, including extracorporeal membrane oxygenation (ECMO), in 18 cases (24%), intra-aortic balloon pump (IABP) in 9 (12%), and ventricular assist device (VAD) in 7 cases (9.3%). VAD devices used were Impella in four cases [ 20 , 25 , 34 , 60 ], Bi-VAD in two, and catheter-based VAD in one case [ 18 , 50 , 68 ]. Only 1 out of 17 patients with isolated pericarditis required inotropic/vasopressor support compared to 44 out of 58 myopericarditis cases ( p < 0.001).…”
Section: Resultsmentioning
confidence: 99%
“…Fortunately, there are clinical reports of influenza-induced fulminant myocarditis successfully treated with intravenous peramivir. 46 , 47 Therefore, new studies are warranted to investigate the potential value of antiviral therapies in cases with heart infection in the clinic.…”
Section: Discussionmentioning
confidence: 99%